Unveiling the self-assembly mechanism of moringa (Moringa oleifera Lam.) seed protein amyloid fibrils: A multi-scale study integrating peptidomics and artificial intelligence - Xiaoze Liu; Jin Zhang; Lang Wang; Tao Fei; Xue Lin; Lu Wang (Food Hydrocolloids, 2026)

Storage and reheating strategies for pre-cooked roasted suckling pig: Preserving quality during storage, restoring crispness and flavor upon reheating - Yanpei Huang; Conghui Lang; Zhineng Wang; Panheng Yang; Mengying Xie; Kang Lin; Xi Zheng; Zijian Lu; Jinsheng Fu; Shengmin Liu; Ming Zhang; Haiming Chen (Food Research International, 2026)

Microplastics from catchment to offshore: Salinity gradients and seasonal discharge control estuarine trapping efficiency and tidal reimport - Kazi Belayet Hossain; Junge Wang; Yang Zhou; Xiangrong Xu; Lang Lin; Xiaoshan Zhu; Yang Liu; Bin Chen; Hongwei Ke; Minggang Cai (Water Research, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Accelerating wastewater-based SARS-CoV-2 surveillance using a mobile laboratory in mixed infrastructure regions - Amirmohammad Sakhaei; Soroosh Torabi; Mohammad Dehghan Banadaki; Alexus Rockward; William D. Strike; Soroush Farahbakhsh; David Graf; August Bodin; Amanda Muzzey; Riley Lang; Sara Ignoffo; Sean Haley; et al. (Science of The Total Environment, 2026)

Bacteriophage-based detection of foodborne pathogens: Advances, challenges, and future perspectives - Zichang Zhang; Ziyue Lang; Shoujia Lin; Yige Zhang; Wenjie Tang; Xing Liu; Hongmei Cao (Food Bioscience, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Novel ex-situ functionalized bacterial cellulose-based packaging films with full hydrogen-bonded network for sustainable and bio-safety food preservation - Changqing Zhao; Lang Wu; Jiao Huang; Liguo Yin; Jiawei Wang; Zihao Feng; Lin Bai; Xingxiu Zhao; Zhifeng Zhao; Shengdong Mu (Food Research International, 2026)

Targeted co-delivery of curcumin and TRAIL via engineered extracellular vesicles: a synergistic therapy against resistant cancers - Lang Liu; Jiahong Jiang; Zelin Wu; Xiaoli Wu; Jun Peng; Nuo Xu; Xudong Lin; Ronghui Sun; Yuyi Kang; Changhong Ke; Caijun Zhao; Qilin Huang; et al. (Drug Delivery and Translational Research, 2026)

Key Risk Factor Identification for Deep-Sea Transportation Safety Based on Complex Network Theory - Kun Lang; Xia Liu; Lin Li; Ming Zhong (Journal of Marine Science and Engineering, 2026)
Deep-sea transportation is faced with complex navigation environments, long voyages, limited emergency response resources, and interacting safety risks. Existing studies have mainly focused on individual risk factors, while the correlations and coupling effects among different factors have received insufficient attention. To identify the key risk factors affecting deep-sea transportation safety, this paper proposes a novel key factor identification model based on complex network theory. Firstly, 34 risk factors affecting deep-sea transportation safety are selected from five aspects using a literature analysis method. Secondly, a weighted directed network of risk factors is constructed based on complex network theory. Then, to evaluate the node importance, six node importance evaluation indicators are established, and a node importance evaluation method is proposed by integrating the analytic hierarchy process (AHP), technique for order preference by similarity to an ideal solution (TOPSIS), and gray relational analysis (GRA). Key risk factors are then determined according to the node importance evaluation results. Finally, the effectiveness of the proposed model is verified through a case study. The results show that the top five most critical risk factors are risk of leakage, emergency speed, physical and chemical properties of the cargoes, sense of personnel safety duty, and seasonal route. The findings can provide practical support for maritime authorities, shipping companies, and safety managers in formulating targeted prevention, control, and emergency response measures for deep-sea transportation safety.

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Robust burst bubble recognition in flotation froths via RGB-D imaging and depth-guided feature extraction - Lin Zhao; Zebin Zou; Binbin Dong; Lang Liu; Yongfang Xie; Shiwen Xie (Minerals Engineering, 2026)

Isomer-specific fate of 4-nonylphenols in textile dyeing wastewater treatment: Insights from aqueous–sludge mass balance - Lang Liu; Yanqing Zhao; Jianyi Zhang; Yuanyuan Liu; Jingwen Zeng; Shengtao Ma; Meiqing Lin; Xunan Ning (Journal of Water Process Engineering, 2026)

Transcriptomic and proteomic analysis of MVK variant sites in two subtypes of porokeratosis - Shuqin Lai; Wenjie Zhu; Chunli Lin; Zimeng Guo; Shiqi Chen; Lang Xie; Jie Liu; Zhaolin Zeng; Cong You; Longnian Li (Journal of Applied Genetics, 2026)

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Advances in denitrifying anaerobic methane Oxidation: Emerging insights into the physiology and metabolism - Ruiyan Lang; Yueran Hao; Mingyu Guo; Weibin Li; Yue Zhang; Yanjie Tang; Fengguang Chai; Panpan Liu; Shunyi Li; Lin Li (Bioresource Technology, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

Quantitative research and implications on policy texts of China’s maritime strategic scientific and technological strength: an analysis based on the three-dimensional framework of “instrument–objective–actor” - Xiaoyu Cui; Wanglai Cui; Yiqian Ding; Cheng Lang; Yunjie Zhang; Xiaoxiao Lin (Frontiers in Marine Science, 2026)
This paper constructs a diamond model for expanding national strategic marine scientific and technological capabilities, establishes a three-dimensional analytical framework of “policy instruments—policy objectives—policy actors,” and conducts a quantitative analysis of 229 policy documents using Nvivo 12. The results indicate that existing policy instruments are inadequately aligned with major strategic needs, production factors, and policy objectives; there is an imbalance in the application of instruments and the distribution of actors; and the system exhibits significant institutional endogeneity. The root causes lie in the allocation of powers and responsibilities between the central and local governments and fragmented inter-departmental governance. Based on these findings, the following optimization directions are proposed: enhance the alignment between policy instruments and objectives, and strengthen demand-side incentives to boost supply; use objectives to guide improvements in the quality of factor supply, focusing on talent development and breakthroughs in core technologies; improve the coordination system among laws, regulations, and policies; and restructure the mechanisms for central-local authority allocation and inter-departmental coordination to address the problem of entrenched preferences in instrument selection at the institutional level.

Generation and characterization of the Il11-Cre knock-in mouse - Xuetao Zhou; Zhongliang Xie; Wenjia Liu; Qingye Wang; Huisang Lin; Rongyu Li; Yiming Lang; Jun Chen; Xiao Yang; Yan Teng; Guan Yang (Transgenic Research, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A biomimetic molecular ‘tailor’ hydrogen bonds and ‘guide’ crystal planes to achieve dendritic-free zinc anodes - Haoran Lang; Chunyuan Xiong; Yufan Chen; Qiaoji Zheng; Yu Huo; Heng Zhang; Haoqi Yang; Dunmin Lin (Chemical Engineering Journal, 2026)

Functional reorganization of microbial ecological clusters is associated with citrus soil health enhancement under greenhouse cultivation - Chenhong Liu; Qi Zhao; Lin Zhang; Fuzhi Ke; Xuebin Xu; Senxiang Yu; Jiaping Lang; Tida Ge; Cong Wang; Haoqing Zhang (Plant and Soil, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Ambient temperature separation of PX and MX with MIL-53(Fe) based simulated moving bed - Yi Lang; Lin Li; Bofeng Wei; Yan Yang; Shaoyan Wang (Chemical Engineering Journal, 2026)

Removal of polypropylene microplastics from water by microalgae Desmodesmus sp.: Influences, kinetics and mechanisms - Qing Xie; Xiaoai Lin; Lang Tan; Longzao Luo; Shuang Luo; Xiaosong Tian; Qing Cheng; Shao Zhang; Yujing Wang (Algal Research, 2026)

Research hotspots and evolutionary trends in microalgae-derived EPA production: A bibliometric review - Qingting Weng; Xiaoai Lin; Longzao Luo; Lang Tan; Qin Liu; Shiping Lu; Guosheng Li; Zhou Zhang (Algal Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A novel multimodal combining radiomics and tumor–stroma ratio (TSR) improves diagnosis of gastric cancer peritoneal metastasis - Lin Zhong; Ting Lin; Dong Hou; Hongyun Huang; Shihai Zhou; Yu Lin; Yue Yu; Liangquan Liu; Jing Luo; Fanghai Han; Lang Xie (Clinical & Experimental Metastasis, 2026)

Inhibitory effects and mechanisms of dichloromethane on a biological contact oxidation process for chemical wastewater treatment - Bixiang Nie; Lang Jiang; Fu Wei; Lin Deng; Zheng Chen; Siyu Hua; Qian Zhang (Process Safety and Environmental Protection, 2026)

Mechanistic influence of calcium-rich inorganics in pulp and paper mill sludge on the organics pyrolysis - Fangjun Chen; Jinze Dai; Henrik Ström; Yi Ouyang; Muhammad Shahzad Khurram; Bilainu Oboirien; Lin Lang; Qingang Xiong (Fuel, 2026)

Optimizing process parameters for catalytic steam gasification of Fe-K based biochar toward hydrogen-rich syngas production - Zhihao Yu; Zizhao Guo; Lin Lang; Xiuli Yin; Aimin Wang; Chuangzhi Wu (Fuel, 2026)

Lactoferrin-quercetin synergy: Mechanistic analysis and functional optimization of high internal phase emulsions for 3D food printing with bioactive delivery capabilities - Yanpei Huang; Conghui Lang; Kang Lin; Weijun Chen; Wenxue Chen; Qiuping Zhong; Jianfei Pei; Ying Lv; Rongrong He; Ming Zhang; Haiming Chen (Food Hydrocolloids, 2026)

Enhanced removal of sulfur-containing ions post persulfate advanced oxidation: Interfacial adsorption-mediated foam fractionation process by amphiphilic graphene oxide - Lin Chen; Yunpeng Wang; Yifei Lang; Wen Wen; Zhongping Li; Huazhang Zhao; Yingfu Li; Nan Hu (Water Research, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Synergistic solvent–salt strategy enables high-efficiency dehydration and recovery of 2,3-butanediol from aqueous media - Yuxia Ji; Rongze Lin; Yanyuan Yin; Xuejiao Yang; Rui Lang; Shaoqu Xie; Yanxiong Fang (Journal of Environmental Chemical Engineering, 2025)

The bitterness, biosynthesis, chemical transformation, and antidiabetic activity of cucurbitane-type triterpenoids from bitter gourd (Momordica charantia L.) - Lang Liu; Ziqiang Lin; Xueyi Cai; Yuyu Zhang; Yan Yang; Chunxue Yang; Dong Liang (Food Chemistry, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Review of Geothermal Energy Development Technologies and Application Prospects in Shandong Province, China - Chun-feng Liu; Xia-min Jia; Kun Liang; Lin-zhi Lang; Yan Zhang; Yi-guo Xue; Zhong-chang Qian; Fan-meng Kong (Applied Geophysics, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Seaweeds-derived proteins and peptides: preparation, virtual screening, health-promoting effects, and industry applications - Lu Wang; Lang Wang; Xiaoze Liu; Xue Lin; Tao Fei; Weimin Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Multifaceted characterization of lactoferrin and (−)-epigallocatechin-3-gallate (EGCG) interactions: development of the pickering emulsions for microencapsulated functional foods - Yanpei Huang; Kang Lin; Conghui Lang; Haiming Chen; Wenxue Chen; Qiuping Zhong; Jianfei Pei; Ying Lv; Rongrong He; Ming Zhang; Weijun Chen (Food Research International, 2025)

A microfluidic based stem-loop probes mediated isothermal amplification for multiplex detection of Vibrio parahaemolyticus - Ziyue Lang; Shoujia Lin; Jinmei Li; Zuorong Xie; Hongmei Cao (Food Chemistry, 2025)

Simultaneous inhibition of heterocyclic aromatic amines, advanced glycation end products, acrylamide, and hydroxymethylfurfural in Chinese braised beef by characteristic spices during braising and in vitro digestion - Xiurong Zheng; Iftikhar Hussain Badar; Feibiao Huang; Rongxin Wen; Lin Mei; Yingying Hu; Lang Zhang (Food Chemistry, 2025)

Breaking the monopoly of the Zn(002): Phosphoryl-heterocyclic co-adsorption to promote preferential exposure of Zn(101) crystal plane for dendrite-free Zn metal anodes - Haoran Lang; Chao Li; Jingxin Zhao; Chunyuan Xiong; Lieyuan Zhang; Yijia Luo; Qiaoji Zheng; Xin Tan; Hong Fu; Bingang Xu; Dunmin Lin (Chemical Engineering Journal, 2025)

Quorum sensing molecules promote the nutrients removal in a HN-AD bacteria-Chlorella symbiotic system - Shumin Qin; Bixiang Nie; Fu Wei; Yan Lin; Lang Jiang; Qian Zhang (Chemical Engineering Journal, 2025)

Deformation features and evolution of deep-seated gravitational slope deformation in underdip slate slopes: insights from distinct element modeling - Cheng-Han Lin; Ming-Lang Lin (Landslides, 2025)
Deep-seated gravitational slope deformation (DSGSD) plays a crucial role in shaping landscapes and is a precursor to disastrous rock slope failures, particularly in mountainous regions composed of slate. How can a slate slope’s deep structure and morphology variation correlate to the DSGSD evolution in space and time? Further, what kinematics and deformation displacements can we expect to observe at specific locations in a DSGSD from a monitoring system? This study aims to address these research questions by adopting distinct element modeling, which enables consideration of the anisotropic behavior and structural geometry of slate slopes. We focus on the slate slope with cataclinal features in the Chingjing region, Taiwan, and perform parametric two-dimensional mechanical modeling using synthetic slope models with different slope heights, slope angles, and cleavage dip angles. The results show that an active deformation is initiated by sliding along the cleavages at the crest after the river incision. The deformation then drives the rock masses to topple at the toe of the slope, and a basal shear plane develops gradually in response to the buckling of the cleavages. For the slope model up to 300 m in height, the thickness of the DSGSD block reaches almost 150 m, and a series of potential sliding planes are identified above the basal shear planes as the DSGSD continues. Mechanical modeling reveals that the surficial and subsurface displacement patterns depend on the evolution stage of the DSGSD process and installation locations. Despite the simplifications inherent in the synthetic slope model, the discrete element modeling captures the DSGSD characteristics observed in natural slate slopes. The geometric and kinematic model and generalized statistical results proposed in this study are expected to be applied in monitoring deployment and data interpretation for DSGSD at the regional scale.

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Non-volatile compounds as aroma modulators in Jiangxiang-flavor Baijiu: Regional flavor differentiation and synergistic interactions with volatile aromas - Xiaotong Lyu; Meiyi Zhou; Qian Wang; Lihuan Lang; Kemin Linghu; Chunhui Wei; Liangcai Lin; Paul A. Kilmartin; Cuiying Zhang (Food Chemistry, 2025)

Regulating the coordination distance of solvation structure for high-performance aqueous zinc ion batteries - Yijia Luo; Chao Li; Lieyuan Zhang; Xin Tan; Yi Yang; Bin Xie; Dandan Zhang; Haoran Lang; Xingyu Chen; Xuemei He; Qiaoji Zheng; Xinqiao Wu; et al. (Chemical Engineering Journal, 2025)

Spatiotemporal Analysis of an Estuary’s Environmental Carrying Capacity in Zhejiang, China - Xinying Lin; Yiqun Yang; Xue Wang; Cheng Lang; Guanqiong Ye; Jian Zeng (Coastal Management, 2025)

Atmospheric transport of microplastics from land to sea is inefficient: Evidence from multimedia observations - Xiangrong Xu; Zhen Yuan; Yanxu Zhang; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Eddy Y. Zeng (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Quorum sensing signaling molecules enhance the treatment performance of the HN-AD bacteria-Chlorella symbiotic system in MABR - Shumin Qin; Lin Deng; Yan Lin; Lang Jiang; Xilong Liu; Qian Zhang (Journal of Environmental Management, 2025)

Boosting the initial Coulombic efficiency of Bi2S3-based anode for practical sodium-ion batteries - Lankun Shi; Rongji Jiao; Dawei Lan; Li Wang; Yu Gao; Meng-Fang Lin; Zhongmin Lang; Wenxiu He; Guixiao Jia; Jinlong Cui; Shaohui Li (Chemical Engineering Journal, 2025)

Impact of Open Crop Straw Biomass Burning Emissions on the Air Pollution in the Hunan Province, China: A Case Study - Datong Luo; Lin Luo; Na Wang; Jianxun Wu; Lang Liu (Aerosol Science and Engineering, 2025)
Emissions from open crop straw burning (OCSB) during crop harvest have exerted considerable impacts on the air quality in China, but the quantitative evaluation of OCSB to air pollutants remains insufficient. In the study, the WRF-Chem model is used to quantitatively evaluate the impacts of OCSB on the air quality in Hunan, China from October 15 to 26, 2024. During the study episode, OCSB contributes 45.7% and 16.8% of the anthropogenic emission of organic carbon and non-methane volatile organic compounds, respectively. Model simulations show that OCSB emissions account for 2.8% of the maximum daily 8-hour average ozone (MDA8 O 3 ) concentration, but play a more substantial role in particulate pollution, contributing 25.6% to near-surface fine particulate matter levels. OCSB is an important organic aerosol (OA) source, increasing primary OA by 46.2% and secondary OA by 62.7%. The enhanced OA accounts for 54.8% of the total PM 2.5 increase induced by OCSB emissions. Sensitivity experiments show that the concentrations of aerosol species generally decrease linearly with reduced OCSB emissions, while MDA8 O 3 concentrations exhibit a non-linear trend due to the complex responses to its precursors. Implementing the clean disposal of straw residue during crop harvest presents an effective strategy to improve the air quality in Hunan.

Performance evaluation of R1336mzz(Z)/TEGDME absorption chiller coupled with low temperature proton exchange membrane fuel cell system - Yufan Yang; Chunhuan Luo; Chunting Zhou; Muran He; Lin Lang; Xi Yu; Changchang Yang; Yufan Chen (International Journal of Refrigeration, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Impact of filtration processes on the key chemical components of Shanxi aged vinegar - Ping Lin; Fanfan Lang; Yufeng Yan; Jian Chen; Zheng Peng; Juan Zhang (Food Bioscience, 2025)

Implicit Difference Solution for One-Dimensional Consolidation of Unsaturated Soil: Numerical Verification and Application to Soil-Cushion System - Qian He; Quan Yuan; Lin Lang; Jixing Cao (Mathematical Geosciences, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

A hairpin reporters-based one-pot LAMP-CRISPR/Cas12a assay for the highly sensitive and visual detection of Vibrio parahaemolyticus - Jinmei Li; Shoujia Lin; Ziyue Lang; Gaowa Xing; Yanwei Jia; Hongmei Cao (Food Control, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Characteristics of Impact Fragmentation and Energy Dissipation of Cylindrical Rock Specimens with Various Aspect Ratios - Yuzhong Qin; Lin Lang; Shuang Tian; Tong Wu; Huaizi Tang; Jun Xu; Yingda Zhang; Jingmei Wang; Huijun Lu; Zheming Zhu (Rock Mechanics and Rock Engineering, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Perovskite quantum dots Revolutionize Lithium-Sulfur battery Performance: Cathode catalytic Breakthrough with CsPbBr3 - Renjing Duan; Xiaoshi Lang; Xiang Wang; Lan Li; Tingting Qu; Lin Wang; Jianbin Li; Chuangang Yao; Kedi Cai (Chemical Engineering Journal, 2025)

Energy consumption and environmental impact analysis of biomass graded deconstruction activation catalytic deoxygenation for rich single-ring aromatic bio-oil preparation - Fengchao Wang; Bin Xu; Lin Lang; Cui Quan; Huacai Liu; Weizhen Li; Wenshen Yang; Ningbo Gao; Xiuli Yin (Bioresource Technology, 2025)

Experimental study on interaction between epizoic diatoms and Pseudodiaptomus annandalei - Jinchun Lin; Lang Li; Xuesong Li; Changping Chen; Junrong Liang; Chengwen Wang; Ruixiang Wu; Lin Sun; Yahui Gao (Journal of Oceanology and Limnology, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Long-term organic farming improves the red soil quality and microbial diversity in subtropics - Yongkang Wen; Wei Yao; Taobing Yu; Lang Cheng; Qing Zhang; Jida Yang; Fangding Lin; Hongye Zhu; Anna Gunina; Yadong Yang; Kevin Z. Mganga; Zhaohai Zeng; et al. (Agriculture, Ecosystems & Environment, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Shear behavior of precast recycled lump-aggregate concrete laminated beams using inclined-crossed stirrups - Lang Lin; Bo Wu (Engineering Structures, 2025)

Improving synergistic catalysis of CuOx/AgOy/TiO2 for promoting selective catalytic oxidation of ammonia - Junfei Chen; Zhihao Yu; Jinwei Wu; Zhao-Bin Ding; Lin Lang; Lining Fang; Xiuli Yin; Zebao Rui (Chemical Engineering Journal, 2025)

Microplastics in the seawater of the Beibu Gulf, the northern South China Sea: occurrence, sources, and ecological risk - Zuhao Zhu; Qiongyuan Su; Huihua Wei; Lang Lin; Liangliang Huang (Journal of Oceanology and Limnology, 2025)

Temporal dynamics of bacterial biofilms and their relationship with heavy metals on expanded polystyrene microplastics - Qun Xie; Yan Feng; Xiangrong Xu; Hengxiang Li; Lang Lin; Weiqiong Yu; Guanghui Zhu; Nenghao Zhong; Minhua Wu; Kai Zhang (Journal of Oceanology and Limnology, 2025)

Distribution and bi-directional transport of surface sediments driven by monsoons on the northwest continental shelf of the South China Sea - Anqi Wang; Lin Zhang; Xiaoqi Chen; Xiting Liu; Hongyuan Lang; Zheng Xu; Cheng Xu; Xianqing Wang; Fangjian Xu (Geo-Marine Letters, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Evaluating and locating a suitable bedrock drilling site near zhongshan station with airborne and ground-based observations - Yanjun Li; Xiangbin Cui; Gang Qiao; Lin Li; Shinan Lang (Polar Science, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

Circular economy-based integrated closed-loop farming system: A sensitivity analysis for profit optimization - Shiou-Yun Jeng; Chun-Wei R. Lin; Kanchana Sethanan; Hsun Wei Wang; Ming-Lang Tseng (Journal of Cleaner Production, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

The experimental study on supercritical CO2 thermochemical reduction of eucalyptus sawdust - Yimeng Wei; Qingang Xiong; Lin Lang; Hui Jin (Fuel, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

A target-triggered domino platform for multimode-guided lateral flow immunoassay of multiple β-agonists - Biao Zhang; Yihan Lang; Xuecheng Zhang; Chenxu Zhang; Yulou Qiu; Kai Sun; Xuping Shentu; Xiaoping Yu; Xiaodong Lin (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Selective and Sensitive Detection of Hg2+ and Ag+ by a Fluorescent and Colorimetric Probe with Large Stokes Shift - Hongqi Li; Jiabao Yan; Lin Jiang; Yong Zhao; Yanxi Song; Jirui Yu; Lang Cheng (Journal of Fluorescence, 2024)

Experimental study on the burning characteristics and smoke temperature distribution of continuous spill fires in sloped tunnels - Weibing Jiao; Changkun Chen; Zida Lin; Yipeng Bao; Lang Shi (Tunnelling and Underground Space Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Primary productivity recovery and shallow-water oxygenation during the Sturtian deglaciation in South China - Xubin Wang; Lin Dong; Haoran Ma; Xianguo Lang; Ruimin Wang (Global and Planetary Change, 2024)

Synergistic interaction of vortex capture and fluid shear in Ni-rich cathode precursor growth process - Yuting Deng; Yi Wang; Lang Qiu; Hongyu Lin; Mengke Zhang; Junbo Zhou; Fuqiren Guo; Benhe Zhong; Yang Song; Xiaodong Guo (Chemical Engineering Journal, 2024)

The role of ferroptosis in DM-induced liver injury - Keping Wu; Jiasi Chen; Jiawen Lin; Enyi Zhu; Xiaochang Xu; Xiuhong Yan; Lang Ju; Mingcheng Huang; Yimin Zhang (BioMetals, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Online estimation of vertical velocity for deep-sea carriers based on depth data - Jichao Lang; Hao Gao; Yang Lin; Haitao Gu (Ocean Engineering, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

A SHAP machine learning-based study of factors influencing urban residents' electricity consumption - evidence from chinese provincial data - Yuanping Wang; Lang Hu; Lingchun Hou; Lin Wang; Juntao Chen; Yu He; Xinyue Su (Environment, Development and Sustainability, 2024)

Regional coordinated development policy as an instrument for alleviating land finance dependency: Evidence from the urban agglomeration development - Danling Chen; Yuying Li; Chaozheng Zhang; Yunlei Zhang; Jiao Hou; Yaoben Lin; Shiman Wu; Yan Lang; Wenbo Hu (Land Use Policy, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

CO2 fluxes contrast between aquaculture ponds and mangrove forests and its implications for coastal wetland rehabilitation in Leizhou Peninsula, China - Ruikun Gou; Jianxiang Feng; Haichao Zhou; Tao Lang; Jiayu Zhao; Lidong Mo; Shanshan Song; Guanghui Lin (Agriculture, Ecosystems & Environment, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Comprehensive kinetic modeling and product distribution for pyrolysis of pulp and paper mill sludge - Fangjun Chen; Lei Ding; Yongfeng Zhu; Guanlong Ren; Yi Man; Kun Hong; Lin Lang; Henrik Ström; Qingang Xiong (Science of The Total Environment, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Safety Analysis of Initial Separation Phase for AUV Deployment of Mission Payloads - Zhengwei Wang; Haitao Gu; Jichao Lang; Lin Xing (Journal of Marine Science and Engineering, 2024)
This study verifies the effects of deployment parameters on the safe separation of Autonomous Underwater Vehicles (AUVs) and mission payloads. The initial separation phase is meticulously modeled based on computational fluid dynamics (CFD) simulations employing the cubic constitutive Shear Stress Transport (SST) k-ω turbulence model and overset grid technologies. This phase is characterized by a 6-degree-of-freedom (6-DOF) framework incorporating Dynamic Fluid-Body Interaction (DFBI), supported by empirical validation. The SST k-ω turbulence model demonstrates superior performance in managing flows characterized by adverse pressure gradients and separation. DFBI entails computationally modeling fluid–solid interactions during motion or deformation. The utilization of overset grids presents several advantages, including enhanced computational efficiency by concentrating computational resources solely on regions of interest, simplified handling of intricate geometries and moving bodies, and adaptability in adjusting grids to accommodate changing simulation conditions. This research analyzes mission payloads’ trajectories and attitude adjustments after release from AUVs under various cruising speeds and initial release dynamics, such as descent and angular velocities. Additionally, this study evaluates the effects of varying ocean currents at different depths on separation safety. Results indicate that the interaction between AUVs and mission payloads during separation increases under higher navigational speeds, reducing the separation speed and degrading the stability. As the initial drop velocities increase, fast transition through the AUV’s immediate flow field promotes separation. The core of this process is the initial pitch angle management upon deployment. Optimizing initial pitching angular velocity prolongs the time for mission payloads to reach their maximum pitch angle, thus decreasing horizontal displacement and improving separation safety. Deploying AUVs at greater depths alleviates the influence of ocean currents, thereby reducing disturbances during payload separation.

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

A sea urchin-shaped nanozyme mediated dual-mode immunoassay nanoplatform for sensitive point-of-care testing histamine in food samples - Biao Zhang; Jingyi Zhang; Yihan Lang; Zicheng Wang; Danfeng Cai; Xiaoping Yu; Xiaodong Lin (Food Chemistry, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Yuzaoea gen. nov., a new biraphid diatom (Bacillariophyceae) genus and its phylogenetic significance - Honghan Liu; Chenhong Li; Lang Li; Xuesong Li; Lin Sun; Junrong Liang; Jun Zhang; Yahui Gao; Changping Chen (Acta Oceanologica Sinica, 2024)

Multi‐ecosystem services differently affected by over‐canopy and understory nitrogen additions in a typical subtropical forest - Yang Tian; Peng Zhou; Lang Zhou; Lei Zhang; Yongbiao Lin; Yanjia Wang; Jun Wang; Dafeng Hui; Hai Ren; Hongfang Lu (Global Change Biology, 2024)
Obtaining a holistic understanding of the impacts of atmospheric nitrogen deposition on multiple ecosystem services of forest is essential for developing comprehensive and sustainable strategies, particularly in heavy N deposition regions such as subtropical China. However, such impacts remain incompletely understood, with most previous studies focus on individual ecosystem function or service via understory N addition experiments. To address this knowledge gap, we quantified the effects of over‐canopy and understory N additions on multiple ecosystem services based on a 7‐year large‐scale field experiment in a typical subtropical forest. Our results showed continued over‐canopy N addition with 50 kg ha −1 year −1 over a period of 4–7 years significantly increased plant nutrient retention, but did not affect the services of soil nutrient accumulation, water yield, C sequestration (in plants and soil), or oxygen release. There were trade‐offs between the soil and plant on providing the services of nutrient accumulation/retention and C sequestration under over‐canopy N addition. However, without uptake and retention of tree canopy, the trade‐off between soil and plant were more weaken under the understory N addition with 50 kg ha −1 year −1 , and their relationships were even synergetic under the understory N addition with 25 kg ha −1 year −1 . The results suggest that understory N addition cannot accurately simulate the effects of atmospheric N deposition on multiple services, along with mutual relationships. Interestingly, the services of plant N, P retention, and C sequestration exhibited a synergetic increase under the over‐canopy N addition but a decrease under the understory N addition. Our results also found tree layer plays a primary role in providing plant nutrient retention service and is sensitive to atmospheric N deposition. Further studies are needed to investigate the generalized effects of forest canopy processes on alleviating the threaten of global change factors in different forest ecosystems.

Influence of Emission-Control Areas on the Eco-Shipbuilding Industry: A Perspective of the Synthetic Control Method - Lang Xu; Zeyuan Zou; Lin Liu; Guangnian Xiao (Journal of Marine Science and Engineering, 2024)
Annex VI of the International Convention for the Prevention of Pollution from Ships (MARPOL Convention), adopted in October 2008, was dedicated to addressing environmental issues caused by ships, especially in ports, inland waterways, and some sea areas with concentrated routes and high navigational density. This study utilizes a regional-level ship dataset to assess the influences of emission-control areas (ECAs) on the ecological shipbuilding industry by fitting the policy utility through the synthetic control method and testing robustness via the difference-in-differences method. The outcomes of this study show that the cumulative new orders for eco-designed ships in China, The Netherlands, Republic of Korea, the UK, and the USA increased by 3401, 81, 234, 549, and −1435, respectively, after the implementation of ECAs. Compared to the implementation of ECAs, the increases were about 32%, 20%, 41%, 66%, and −83%, respectively.

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Multi-scale numerical simulations of the synoptic environment, Diablo windstorm, and wildfire formation mechanisms for the Tubbs Fire (2017) - Jackson T. Wiles; Yuh-Lang Lin; Michael L. Kaplan (Meteorology and Atmospheric Physics, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

Isomer-specific analysis of nonylphenol and their transformation products in environment: A review - Jianyi Zhang; Lang Liu; Xunan Ning; Meiqing Lin; Xiaojun Lai (Science of The Total Environment, 2023)

Study on energy consumption, thermal comfort and economy of passive buildings based on multi-objective optimization algorithm for existing passive buildings - Yuanping Wang; Lang Hu; Lingchun Hou; Weiguang Cai; Lin Wang; Yu He (Journal of Cleaner Production, 2023)

Improvement of membrane-forming ability and separation performance of hydroxylated BN membrane by GO via π-π interaction - Lin-Lin Ye; Xi Chen; Yan Chen; Xi Yan; Xiao-Jing Guo; Wan-Zhong Lang (Desalination, 2023)

Heterogeneous photocatalysis coupled with Fenton-Like reaction for fluoroquinolone antibiotics degradation by poly (Triazine Imide): From mechanism to application in a continuous flow catalytic system - Jingjun Qin; Zhang Liu; Weicheng Xu; Ximiao Zhu; Fawen Liang; Yutang Yu; Yuanzhi Zheng; Lang Yao; Honghua Zhang; Kaichun Lin; Jianzhang Fang; Zhanqiang Fang (Chemical Engineering Journal, 2023)

Morph-genetic biomimetic multiscale porous hydrogels for high-efficient solar evaporation from seawater - Lin Chen; Yue Sun; Chao Ma; Ye Sun; Shuyi Peng; Xingyu Cao; Lang Yang; Chunxin Ma; Hongliang Zhao; Hao Wang; Dong Zhang; Qijie Liu; et al. (Chemical Engineering Journal, 2023)

Evaporative emission characteristics of VOCs from in-use light-duty gasoline vehicles - Teng Zi; Pengrui Wang; Baoxian Liu; Ying Zhou; Xiu'e Shen; Lin Zhang; Yang Lu; Qian Feng; Yanyan Yang; Jianlei Lang (Atmospheric Environment, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Inactivation of Alicyclobacillus acidoterrestris vegetative cells and spores induced by atmospheric cold plasma - Si-Qi Zhao; Lin Chen; Bing Yan; Lang-Hong Wang; Xin-An Zeng; Rana Muhammad Aadil (Innovative Food Science & Emerging Technologies, 2023)

Electronic regulation and hydrophobicity improvement of the palladium active site by ionic liquid to achieve high selectivity direct synthesis of hydrogen peroxide - Lang Wu; Hong Qin; Songhua Zhou; Ziming Luo; Yang Xiao; Huan You; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Identification of Genes Related to Resistance to Ichthyophthirius multifiliis Based on Co-expression Network Analysis in Grass Carp - Feng Chen; Wei Zhang; Xiaoyan Xu; Lang Gui; Yanfeng Lin; Minglin Wu; Jiale Li; Yubang Shen (Marine Biotechnology, 2023)

Environmentally relevant levels of BPA and NOR disturb early skeletal development in zebrafish - Lin Duan; Haoyang Deng; Qianqing Zhang; Peijie Gao; Lang Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Sequential deacetylation/self-gelling chitin hydrogels and scaffolds functionalized with fucoidan for enhanced BMP-2 loading and sustained release - Hsien-Tsung Lu; Chi Lin; Yi-Ju Wang; Fang-Yu Hsu; Ju-Ting Hsu; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Dynamic Process Study of Earthquake-Induced Landslides Applying an Improved Discontinuous Deformation Analysis Method Considering Site Response - Jinmei Wang; Yingbin Zhang; Pengcheng Yu; Bo Shu; Qingdong Wang; Yong Xu; Lin Lang; Xinyan Peng (Rock Mechanics and Rock Engineering, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Durable dual-methylpiperidinium crosslinked poly(binaphthyl-co-terphenyl piperidinium) anion exchange membranes with high ion transport and electrochemical performance - Wei Ting Gao; Xue Lang Gao; Yvonne Shuen Lann Choo; Jia Jun Wang; Zhi Hong Cai; Qiu Gen Zhang; Ai Mei Zhu; Qing Lin Liu (Chemical Engineering Journal, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Distribution of environmentally persistent free radicals in size-segregated PMs emitted from residential biomass fuel combustion - Jinfeng Zhao; Lin Shi; Jianwu Shi; Hao Li; Di Lang; Zhuo Wei; Shunling Li; Bo Pan (Journal of Hazardous Materials, 2023)

Storm-driven variations in depositional environments modify pyrite sulfur isotope records - Kaixi Jiang; Chunming Lin; Xia Zhang; Yanyan Zhao; Xianguo Lang; Ming Su; Ce Wang; Yaping Lei; Jiarui Liu (Earth and Planetary Science Letters, 2023)

Resource saving and carbon footprint reduction potential of urban symbiosis strategy in express packaging waste recycling network - Yuhe Shi; Yun Lin; Songyi Wang; Haolin Wen; Ming K. Lim; Ming-Lang Tseng (Waste Management, 2023)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

The impacts of assimilating CFOSAT scatterometer winds for Typhoon cases based on real-time rain quality control - Yaodeng Chen; Yemeng Cui; Wenming Lin; Jianqiang Liu; Congrong Sun; Shuyan Lang (Atmospheric Research, 2023)

Potential of kerosene-diesel blends as alternative fuels for diesel engines: Perspectives from spray combustion characteristics - Zhaowen Wang; Xiaojie Li; Lin Xiang; Yuhan Huang; Bing Lang; Xiaobei Cheng; Jie Zhang (Fuel, 2023)

ReaxFF molecular dynamics study of co-combustion of waste tires with petroleum coke gasification residue: Combustion characteristics, gas evolution and micro mechanism - Xiuxia Zhang; Lining Liu; Bofan Lang; Lianxin Xia; Riyi Lin; Xinwei Wang (Fuel, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Microplastic contamination in coral reef fishes and its potential risks in the remote Xisha areas of the South China Sea - Lei Huang; Qian P. Li; Hengxiang Li; Lang Lin; Xiangrong Xu; Xiaojie Yuan; Jayamini B. Koongolla; Huawei Li (Marine Pollution Bulletin, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Two silver energetic coordination polymers based on a new N-amino-contained ligand: Towards good detonation performance and excellent laser-initiating ability - Qing Lang; Xinyi Li; Jianxin Zhou; Yuangang Xu; Qiuhan Lin; Ming Lu (Chemical Engineering Journal, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Spatiotemporal impacts of climate change and human activities on water resources and ecological sensitivity in the Mekong subregion in Cambodia - Yi Lin; Yu Rong; Lang Li; Fengting Li; Hanchao Zhang; Jie Yu (Environmental Science and Pollution Research, 2023)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Feng Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

Correction: Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Tao Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

Identification and molecular mapping of YrBm for adult plan resistance to stripe rust in Chinese wheat landrace Baimangmai - Chaoyue Hu; Fengtao Wang; Jing Feng; Cai Sun; Jiyuan Guo; Xiaowei Lang; Jinghuang Hu; Bin Bai; Wentao Zhang; Hongjie Li; Ruiming Lin; Shichang Xu (Theoretical and Applied Genetics, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Identification of Hub Genes Associated with Abnormal Endothelial Function in Early Coronary Atherosclerosis - Xue Qiu; Jinyan Lin; Yanbing Chen; Bixiao Liang; Lang Li (Biochemical Genetics, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Effects of Microplastics on Microbial Community in Zhanjiang Mangrove Sediments - Meng-Meng Chen; Fang-Hong Nie; Aftab Qamar; Di-hua Zhu; Yao Hu; Min Zhang; Qing-Lang Song; Hong-Ying Lin; Zhi-Bao Chen; Su-Qing Liu; Jin-Jun Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Ameliorating Effect of Umbilical Cord Mesenchymal Stem Cells in a Human Induced Pluripotent Stem Cell Model of Dravet Syndrome - Huifang Zhao; Shuai Li; Lang He; Feng Tang; Xiaobo Han; Weiyue Deng; Zuoxian Lin; Rongqi Huang; Zhiyuan Li (Molecular Neurobiology, 2022)

Glomalin-related soil protein (GRSP) in metal sequestration at Pb/Zn-contaminated sites - Lang Qiu; Hanzhi Lin; Benru Song; Tianle Kong; Weimin Sun; Xiaoxu Sun; Yanxu Zhang; Baoqin Li (Journal of Soils and Sediments, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Citric acid and AMF inoculation combination–assisted phytoextraction of vanadium (V) by Medicago sativa in V mining contaminated soil - Lang Qiu; Wenlong Gao; Zhigang Wang; Baoqin Li; Weimin Sun; Pin Gao; Xiaoxu Sun; Benru Song; Yanxu Zhang; Tianle Kong; Hanzhi Lin (Environmental Science and Pollution Research, 2021)

Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary: abundance, size, surface texture and their metals-carrying capacity - Qun Xie; Heng-Xiang Li; Lang Lin; Zhen-Liang Li; Jian-sheng Huang; Xiang-Rong Xu (Ecotoxicology, 2021)

The ATP Level in the mPFC Mediates the Antidepressant Effect of Calorie Restriction - Qian Wang; Ying Kong; Song Lin; Ding-Yu Wu; Jian Hu; Lang Huang; Wen-Si Zang; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

The hand-arm vibration syndrome associated with the grinding of handheld workpieces in a subtropical environment - Nuoyan Wei; Hansheng Lin; Ting Chen; Bin Xiao; Maosheng Yan; Li Lang; Hongyu Yang; Shan Wu; Paul-Émile Boileau; Qingsong Chen (International Archives of Occupational and Environmental Health, 2021)

Orographic effects on the propagation and rainfall modification associated with the 2007–08 Madden–Julian oscillation (MJO) past the New Guinea Highlands - Yuh-Lang Lin; William Agyakwah; Justin G. Riley; Huang-Hsiung Hsu; Li-Chiang Jiang (Meteorology and Atmospheric Physics, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Wind speed inversion and in-orbit assessment of the imaging altimeter on Tiangong-2 space station - Youguang Zhang; Qingliu Bao; Mingsen Lin; Shuyan Lang (Acta Oceanologica Sinica, 2020)

Transient receptor potential ankyrin 1 contributes to the ATP-elicited oxidative stress and inflammation in THP-1-derived macrophage - Chao Tian; Xiaobo Han; Lang He; Feng Tang; Rongqi Huang; Zuoxian Lin; Shuai Li; Sihao Deng; Junjie Xu; Hualin Huang; Huifang Zhao; Zhiyuan Li (Molecular and Cellular Biochemistry, 2020)

Correction to: Investigating the age composition of Indo-Pacific humpback dolphins in the Pearl River Estuary based on their pigmentation pattern - Lang Guo; Wenzhi Lin; Chen Zeng; Dingyu Luo; Yuping Wu (Marine Biology, 2020)

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Comprehensive Geophysical Investigation and Analysis of Lining Leakage for Water-Rich Rock Tunnels: A Case Study of Kaiyuan Tunnel, Jinan, China - Chunjin Lin; Xintong Wang; Lichao Nie; Huaifeng Sun; Zhenhao Xu; Yuchao Du; Lang Liu (Geotechnical and Geological Engineering, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Investigating the age composition of Indo-Pacific humpback dolphins in the Pearl River Estuary based on their pigmentation pattern - Lang Guo; Wenzhi Lin; Chen Zeng; Dingyu Luo; Yuping Wu (Marine Biology, 2020)

Protoraphis Simonsen, a newly recorded marine epizoic diatom genus for China - Lang Li; Changping Chen; Lin Sun; Jiawei Zhang; Junrong Liang; Yahui Gao (Acta Oceanologica Sinica, 2020)

High dietary lipid level alters the growth, hepatic metabolism enzyme, and anti-oxidative capacity in juvenile largemouth bass Micropterus salmoides - Yue-Lang Zhou; Jia-Ling Guo; Ren-Jun Tang; Hui-Jia Ma; Yong-Jun Chen; Shi-Mei Lin (Fish Physiology and Biochemistry, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Failure mechanism of a mudstone slope embedded with steep anti-dip layered sandstones: case of the 2016 Yanchao catastrophic landslide in Taiwan - Cheng-Han Lin; Ching Hung; Meng-Chia Weng; Ming-Lang Lin; Ryosuke Uzuoka (Landslides, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Influences of Appalachian orography on heavy rainfall and rainfall variability associated with the passage of hurricane Isabel by ensemble simulations - Guy Oldaker; Liping Liu; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2019)

On the coupling of convective updrafts prior to secondary eyewall formation in Hurricane Katrina (2005) - Jose M. Garcia-Rivera; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2019)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Looping tracks associated with tropical cyclones approaching an isolated mountain. Part I: Essential parameters - Yi-Chih Huang; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Different effects of low- and high-dose waterborne zinc on Zn accumulation, ROS levels, oxidative damage and antioxidant responses in the liver of large yellow croaker Pseudosciaena crocea - Jia-Lang Zheng; Lin Zeng; Mei-Ying Xu; Bin Shen; Chang-Wen Wu (Fish Physiology and Biochemistry, 2017)

Effects of β-glucan on ROS production and energy metabolism in yellow croaker (Pseudosciaena crocea) under acute hypoxic stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Jia-Lang Zheng; Chang-Wen Wu; Rong Cai (Fish Physiology and Biochemistry, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Tropical Storm Kyle (2002) and cold-air damming: their interactions and impacts on heavy rainfall in the Carolinas - Jose M. Garcia-Rivera; Yuh-Lang Lin; Yevgenii Rastigejev (Meteorology and Atmospheric Physics, 2016)

Efficacy of dexmedetomidine with cognitive behavioral therapy for treating chronic insomnia related to conditioned arousal: a randomized controlled trial - Xunjun Li; Xiaojiang Jiang; Yazhen Liu; Ying Lang; Yuanyuan Ye; Ling Lin; Juan Liu; Yuanfeng Zhang (Sleep and Biological Rhythms, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Effects of the subtropical anticyclones over North Africa and Arabian Peninsula on the African easterly jet - James Spinks; Yuh‐Lang Lin; Ademe Mekonnen (International Journal of Climatology, 2015)
North African climate is analysed between 1979 and 2010 with an emphasis on August using the European Center for Medium‐Range Weather Forecast ( ECMWF ) global dataset to investigate the effects of the subtropical anticyclones over North Africa and the Arabian Peninsula on the African easterly jet ( AEJ ). It was found that the AEJ encloses a core with a local wind maximum ( LWM ) in both West and East Africa, in which the west LWM core has a higher zonal wind speed. The strength of both cores is distinctly different by way of thermal wind balance. As found in previous studies, the AEJ is formed through baroclinicity with influence from Saharan lower level heating along and to the north of the Intertropical Front ( ITF ). As there are two separate anticyclonic centres, the AEJ is maintained by the anticyclonic systems in West Africa, East Africa as well as the Arabian Peninsula. The presence of these two anticyclonic centres provides the AEJ with two separate core maxima with the western LWM located at 15°W, 17°N and the eastern LWM located at 35°E, 15°N for August.

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Nonlinear reduction in risk for colorectal cancer by oral contraceptive use: a meta-analysis of epidemiological studies - Nan-Nan Luan; Lang Wu; Ting-Ting Gong; Yong-Lai Wang; Bei Lin; Qi-Jun Wu (Cancer Causes & Control, 2015)

Short-term effects of meteorological factors on children hand, foot and mouth disease in Guangzhou, China - Chun Chen; Hualiang Lin; Xiaoquan Li; Lingling Lang; Xincai Xiao; Peng Ding; Peng He; Ying Zhang; Ming Wang; Qiyong Liu (International Journal of Biometeorology, 2014)

Landslide at Su-Hua Highway 115.9k triggered by Typhoon Megi in Taiwan - Chia-Ming Lo; Ching-Fang Lee; Hsien-Ter Chou; Ming-Lang Lin (Landslides, 2014)

In vitro exposure to copper influences lipid metabolism in hepatocytes from grass carp (Ctenopharyngodon idellus) - Qing-Ling Zhu; Zhi Luo; Mei-Qin Zhuo; Xiao-Ying Tan; Lin-Dan Sun; Jia-Lang Zheng; Qi-Liang Chen (Fish Physiology and Biochemistry, 2014)

A study on the structure and precipitation of Morakot (2009) induced by the Central Mountain Range of Taiwan - Yi-Chih Huang; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2014)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Origin of the pre-tropical storm Debby (2006) African easterly wave-mesoscale convective system - Yuh-Lang Lin; Liping Liu; Guoqing Tang; James Spinks; Wilson Jones (Meteorology and Atmospheric Physics, 2013)

Tracing the origins and propagation of pre-tropical storm Debby (2006) mesoscale convective systems using pattern recognition and image fusion - Chaunté W. Lacewell; Abdollah Homaifar; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2013)

The Hungtsaiping landslides: from ancient to recent - Kuang-Tsung Chang; Ming-Lang Lin; Jia-Jyun Dong; Chang-Hai Chien (Landslides, 2012)

Effect of Ocean Spray on Vertical Momentum Transport Under High-Wind Conditions - Yevgenii Rastigejev; Sergey A. Suslov; Yuh-Lang Lin (Boundary-Layer Meteorology, 2011)

Production of ectoine through a combined process that uses both growing and resting cells of Halomonas salina DSM 5928T - Ya-jun Lang; Lin Bai; Ya-nan Ren; Ling-hua Zhang; Shinichi Nagata (Extremophiles, 2011)

Microarray-based identification of tomato microRNAs and time course analysis of their response to Cucumber mosaic virus infection - Qiu-lei Lang; Xiao-chuan Zhou; Xiao-lin Zhang; Rafal Drabek; Zhi-xiang Zuo; Yong-liang Ren; Tong-bin Li; Ji-shuang Chen; Xiao-lian Gao (Journal of Zhejiang University-SCIENCE B, 2011)

The impact of microphysical schemes on hurricane intensity and track - Wei-Kuo Tao; Jainn Jong Shi; Shuyi S. Chen; Stephen Lang; Pay-Liam Lin; Song-You Hong; Christa Peters-Lidard; Arthur Hou (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Blocking NF-κB and Akt by Hsp90 inhibition sensitizes Smac mimetic compound 3-induced extrinsic apoptosis pathway and results in synergistic cancer cell death - Lang Bai; Shanling Xu; Wenshu Chen; Zi Li; Xia Wang; Hong Tang; Yong Lin (Apoptosis, 2011)

Downregulation of CREB-binding protein expression sensitizes endothelial cells to serum-deprived apoptosis: important role of nitric oxide - Jing Chen; Hong Jiang; Li-hua Zhu; Lang Wang; Lin Xu (Molecular and Cellular Biochemistry, 2010)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

Application of fuzzy DEMATEL to develop a cause and effect model of municipal solid waste management in Metro Manila - Ming-Lang Tseng; Yuan Hsu Lin (Environmental Monitoring and Assessment, 2009)

Probabilistic Ecological Risk Assessment and Source Apportionment of Polycyclic Aromatic Hydrocarbons in Surface Sediments from Yellow Sea - Ai-Xia Liu; Yin-Hai Lang; Li-Dong Xue; Shu-Lin Liao; Hong Zhou (Bulletin of Environmental Contamination and Toxicology, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jen Liu (Apoptosis, 2009)

Bovine ephemeral fever virus-induced apoptosis requires virus gene expression and activation of Fas and mitochondrial signaling pathway - Chi-Hung Lin; Wen-Ling Shih; Feng-Lang Lin; Yao-Ching Hsieh; Yur-Ren Kuo; Ming-Huei Liao; Hung-Jeng Liu (Apoptosis, 2009)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Bioavailability Effect of Methylprednisolone by Polymeric Micelles - Ching-Lin Chen; Shwu-Fen Chang; Daniel Lee; Lang-Yo Yang; Yi-Hsuan Lee; Chung Y. Hsu; Shwu-Jiuan Lin; Jiahorng Liaw (Pharmaceutical Research, 2008)

Fiber type and myosin heavy chain compositions of adult pretarsal orbicularis oculi muscle - Nai-Chen Cheng; Shu-Lang Liao; I-Jong Wang; I-Chan Lin; Yueh-Bih Tang (Journal of Molecular Histology, 2007)

Streptomyces roseoalbus sp. nov., an actinomycete isolated from soil in Yunnan, China - Li-Hua Xu; Yi Jiang; Wen-Jun Li; Meng-Lang Wen; Ming-Gang Li; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Recent advances in dynamical extra-seasonal to annual climate prediction at IAP/CAS - Lin Zhaohui; Wang Huijun; Zhou Guangqing; Chen Hong; Lang Xianmei; Zhao Yan; Zeng Qingcun (Advances in Atmospheric Sciences, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Pharmaceutical development and manufacturing of a parenteral formulation of a novel antitumor agent, VNP40101M - Gopal Krishna; William F. Hodnick; Wengsheng Lang; Xu Lin; Srinivasa Karra; John Mao; Bijan Almassian (AAPS PharmSciTech, 2001)

Large-Eddy Simulations of the Atmospheric Boundary Layer Using a New Subgrid-Scale Model – I. Slightly unstable and neutral cases - Feng Ding; S. Pal Arya; Yuh-Lang Lin (Environmental Fluid Mechanics, 2001)

Large-Eddy Simulations of the Atmospheric Boundary Layer Using a New Subgrid-Scale Model – II. Weakly and moderately stable cases - Feng Ding; S. Pal Arya; Yuh-Lang Lin (Environmental Fluid Mechanics, 2001)

Effects of shear and sharp gradients in static stability on two-dimensional flow over an isolated mountain ridge - Ting-An Wang; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2000)

Variations of bed surface sediment size in a channel bend - Chin-Lien Yen; Yan-Lang Lin (Water, Air, & Soil Pollution, 1997)

Variations of Bed Surface Sediment Size in a Channel Bend - Chin-Lien Yen; Yan-Lang Lin (Water, Air, & Soil Pollution, 1997)